Relation of early-stage renal insufficiency and cardiac structure and function in a large population of asymptomatic Asians: a cross-sectional cohort analysis - Wu, Pei-Chen; Sung, Kuo-Tzu; Lin, Jiun-Lu; Hung, Ta-Chuan; Lai, Yau-Huei; Su, Cheng-Huang; Yeh, Hung-I.; Wu, Chih-Jen; Hung, Chung-Lieh (Frontiers in Nephrology, 2023)
Background: Few studies have addressed early-stage kidney disease and preclinical cardiac structural and functional abnormalities from a large-scale Asian population. Further, the extent to which measures of myocardial function and whether these associations may vary by testing various formulas of renal insufficiency remains largely unexplored. Objective: To explore the associations among renal function, proteinuria, and left ventricular (LV) structural and diastolic functional alterations. Design: A cross-sectional, retrospective cohort study. Setting: Registered data from a cardiovascular health screening program at MacKay Memorial Hospital from June 2009 to December 2012. Participants: Asymptomatic individuals. Measurements: Renal function was evaluated in terms of estimated glomerular filtration rate (eGFR) by both MDRD and CKD-EPI formulas and severity of proteinuria, which were further related to cardiac structure, diastolic function (including LV e’ by tissue Doppler), and circulating N-terminal pro-brain natriuretic peptide (NT-proBNP) level. Results: Among 4942 participants (65.8% men, mean age 49.4±11.2 years), the mean CKD-EPI/MDRD eGFR was 90.6±15.7 and 88.5±16.9 ml/min/1.73m2, respectively. Lower eGFR, estimated either by the MDRD or CKD-EPI method, and higher proteinuria were significantly associated with lower LV e’ and higher NT-proBNP (all p<0.05) even after adjusting for clinical covariates. In general, lower eGFR estimated by CKD-EPI and MDRD displayed similar impacts on worsening e’ and NT-proBNP, rather than E/e’, in multivariate models. Finally, lower LV e’ or higher composite diastolic score, rather than E/e’, demonstrated remarkable interaction with eGFR level estimated by either CKD-EPI or MDRD on circulating NT-proBNP level (p interaction <0.05). Limitations: Proteinuria was estimated using a urine dipstick rather than more accurately by the urine protein-to-creatinine ratio. Also, pertaining drug history and clinical hard outcomes were lacking. Conclusion: Both clinical estimate of renal insufficiency by eGFR or proteinuria, even in a relatively early clinical stage, were tightly linked to impaired cardiac diastolic relaxation and circulating NT-proBNP level. Elevation of NT-proBNP with worsening renal function may be influenced by impaired myocardial relaxation.